Acute effects of cocaine on the neurobiology of cognitive control - GARAVAN, HUGH PATRICK (Royal Society Publishing, 2008)
Compromised ability to exert control over drug urges and drug-seeking behaviour is a characteristic of addiction. One specific cognitive control function, impulse control, has been shown to be a risk factor for the development of substance problems and has been linked in animal models to increased drug administration and relapse. We present evidence of a direct effect of cocaine on the neurobiology underlying impulse control. In a laboratory test of motor response inhibition, an intravenous cocaine administration improved task performance in 13 cocaine users. This improvement was accompanied by increased activation in right dorsolateral and inferior frontal cortex, regions considered critical for this cognitive function. Similarly, for both inhibitory control and action monitoring processes, cocaine normalized activation levels in lateral and medial prefrontal regions previously reported to be hypoactive in users relative to drug-naive controls. The acute amelioration of neurocognitive dysfunction may reflect a chronic dysregulation of those brain regions and the cognitive processes they subserve. Furthermore, the effects of cocaine on midline function suggest a dopaminergically mediated intersection between cocaine's acute reinforcing effects and its effects on cognitive control.
PUBLISHED
Keywords: cocaine impulsivity functional magnetic resonance imaging addiction